Gastrointestinal Parasitism In Kedah-Kelantan Calvesincidence, Effect On Growth And Cost- Benefit Of Anthelmintics - Panchadcharam, Chandrawathani (1988)
A study of the incidence and effects of gastrointestinal tract parasitism on growth rates and two blood parameters of Kedah-Kelantan was carried out in the Beef Unit, Universiti Pertanian Malaysia. The cost effectiveness of two anthelmintics, oxfendazole and ivermectin was also assessed. A total of 75 newborn Kedah-Kelantan calves were allocated equally into three groups. All the calves grazed with their dams till one year of age, under an improved extensive rotational pasture management. Oxfendazole and ivermectin was administered regularly at the recommended dose rates to the first and second groups respectively. The third group of calves remained as untreated controls. All calves were given an oral coccidiostat. At regular intervals, the calves were weighed and faecal samples were collected for qualitative and quantitative assessment of helminths and coccidia. Blood samples were also taken for packed cell volume, plasma protein and gastrin measurements. Three species of coccidia, nanely Eimeria bovis (more than 80 percent of the calves) , E. zuernii (more than 60 percent of the calves) and E. ellipsoidalis (less than 10 percent of the calves) were identified in the three groups of calves especially during the first six months despite of regular coccidiostat therapy. other parasites such as Toxocara vitulorurn ( found only in 8 percent of the .control calves) and strongyloides papillosus ( more than 80 percent of all calves) were found during the first two and three months respectively. Tapeworm (Moniezia) was present in 44 percent of the ivermectin treated and control groups, and in 24 percent of the oxfendazole treated group. The only strongyle recovered fran faecal culture was Haemonchus placei fourrl in 92 percent of the control calves from three months of age onwards.